Fiber-Reinforced Composites in Rapid Prototyping Technologies; Applied Mechanics and Materials; Vol. 770 : Urgent Problems of Up-to-Date Mechanical Engineering - Saprykin A. A. Aleksandr Aleksandrovich (Materials Science in Mechanical Engineering, 2015)
Title screen